Prosthetic Reconstruction of the Maxilla and Palate - Pool, Christopher; Shokri, Tom; Vincent, Aurora; Wang, Weitao; Kadakia, Sameep; Ducic, Yadranko (Seminars in Plastic Surgery, 2020)
Maxillary defects commonly present following surgical resection of oncologic processes. The use of rotational and free flaps has largely replaced the use of prosthetic options for hard palate and maxillary reconstruction, but prostheses remain a useful tool. Prosthetic devices may be invaluable in patients considered poor candidates for surgical reconstruction secondary to poor vascularity, need for postoperative radiation, or medical comorbidities that place them at high risk for healing following reconstruction. Obturators may also be considered over soft tissue options if oncologic surveillance via direct visualization of the surgical site is warranted.
Keywords: facial reconstruction; prosthetics; prosthesis; maxilla; craniofacial